CLIMATE CHANGE MITIGATION ON FORESTRY BASED ON REED+ IN INTERNATIONAL LAW AND INDONESIA - Sukanda Husin (Fakultas Hukum Universitas Gadjah Mada, 2014)
The Climate Change Convention and the Kyoto Protocol are designated to restrict and reduce the emissions of GHG through three mechanisms, i.e., carbon sinks, bubbling schemes and flexibility mechanisms. All mechanisms are designed for developed countries Parties. The developing countries Parties do not have such obligations. However, the developing countries are given chance to participate in achieving the Protocol’s objectives through REDD+, especially to reduce emissions of carbon dioxide in forestry sector. Indonesia has enacted several regulations for implementing REDD+ Program. To this date, Indonesia has had carbon project mechanisms and succeeded to realize 40 projects in the period of 2008-2012.Keywords: climate change, mitigation, REDD+. Konvensi Perubahan Iklim dan Protokol Kyoto dirancang untuk membatasi dan mengurangi emisi GRK melalui 3 (tiga) mekanisme, yaitu carbon sinks, bubbling schemesdan flexibility mechanisms. Semua mekanisme tersebut ditujukan untuk Pihak negara maju. Negara berkembang tidak dibebani kewajiban seperti itu. Tapi negara berkembang diberi kesempatan untuk berpartisipasi mencapai tujuan Protokol melalui REDD+, yang secara khusus dibuat untuk mengurangi emisi karbon dioksida di sektor kehutanan. Indonesia telah membuat beberapa peraturan untuk menerapkan Program REDD+. Sampai saat ini, Indonesia telah membuat mekanisme proyek karbon dan berhasil mendapatkan 40 proyek dalam kurun waktu 2008-2012.